Is the Crime of Aggression Really Accountable? Reflections about Syria - Carvajal, Ilich Felipe Corredor (International Journal of Criminology and Sociology, 2014)
Nobody can deny that Syria's situation is really serious, and requires an effective solution from the international community. However, that "intervention/solution" will have to respect the UN Charter and the Security Council's responsibilities like the non intervention principle and the new definition of the crime of aggression adopted in Kampala in 2010. This paper analyses the role of major powers (especially the USA and France) and the hypothetic application of the article 8 bis of the Rome Statute, if the Security Council is not able to find a consensus, and a "unilateral" solution was carried out by the aforementioned powerful States.